Middle Lobe Syndrome - Wayan Ferly Aryana; Tito Tri Saputra; Adityo Wibowo (Fakultas Kedokteran, 2023)
Middle Lobe Syndrome (MLS) is a rare condition with significant clinical implications. MLS is characterized by a recurrent or chronic collapse of the right middle lobe of the right lung. MLS is more common in women, with a ratio ranging from 1.5 to 3. MLS is divided into two types: obstructive MLS, caused by enlarged peribronchial lymph nodes, and non-obstructive MLS, which is frequently associated with airway inflammation. Clinical symptoms of MLS include chest pain, chronic cough, excessive sputum, and dyspnea. Symptomatic medication such as mucolytics and bronchodilators, chest physiotherapy, fiberoptic bronchoscopy, and surgery are commonly used as a management of MLS. Keywords: Medial Lobe Syndrome, Obstructive, Chronic Cough